Exploratory Evaluation of Incentives to Increase High-Occupancy Vehicle Use on Priced Highway Facilities. Issue 7 (July 2022) - DeCorla-Souza, Patrick T.; Zahedian, Sara; Nohekhan, Amir; Nejad, Mohammad; Erdogan, Sevgi
This paper introduces an innovative way to incentivize increased person throughput on priced highway facilities such as toll roads, express toll lanes, and high-occupancy toll (HOT) lanes, using cash rewards for carpoolers and transit riders. An exploratory evaluation of the concept is demonstrated for the I-66 HOT facility inside the Capital Beltway in Northern Virginia. The results of the analysis suggest that the concept could provide significant benefits at a relatively low cost to public agencies for cash incentives.